Buddha’s and Krishnamurti’s Teachings to Individual Intelligence to Religious Tolerance and Social Harmony (Rupandehi Campus Journal, 2024)
This paper aims to elaborate the teachings of Buddha and Jiddu Krishnamurti, with a concentration on their importance of individual growth that ultimately results in religious tolerance and social harmony. The literature review reveals that both the Buddha and the contemporary Jidddu Krishnamurti share a common emphasis on the development of the individual as the key to achieving social harmony and religious tolerance. The findings of the author disclose eight themes based on the literature review, including the importance of education. It is crucial for religious organizations, society, experts, scientists, educators, thinkers, decision-makers, politicians, and government officials to comprehend the contributions of Jiddu Krishnamurti and Buddha, and emphasize the multidimensional personal growth that can be achieved through their works. In this paper, the author hopes to contribute to a better understanding of these two great thinkers and their contributions to the promotion of a more peaceful and harmonious world.